Reasons for enrolment, perceived roles, and the educational environment of a Medical Review Center - Banzuela, Enrico Paolo C.
Similar to other professions in the Philippines and abroad, many medical graduates enroll in medical review centers (a.k.a. “commercial coaching centers” or “test preparation centers”) even if medical schools have already certified them as having achieved the competencies needed to practice medicine. This study determined the reasons why medical graduates enroll in review centers, described the perceived roles they fulfilled as well as their educational environment. Respondents are medical graduates enrolled in a Metro Manila-based medical review center in July-September 2019. The study was an explanatory sequential mixed methods design. Quantitative phase of the study used a survey (utilizing Likert-Scales) and the Dundee Ready Education Environment Measure (DREEM) Questionnaire. Qualitative phase was a combination of a survey (using open-ended questions) and focus group discussions. Top reasons for student enrolment include guided preparation, enhanced motivation/confidence, time management, endorsement by seniors,’ board relevant materials, and to pass the medical board examinations. Mechanisms for guided preparation include prescribed schedule, emotional support system, board-relevant materials, engaging board-relevant lectures, testmanship and optimal test-taking strategies and benchmarking opportunities. Top perceived roles include the review center as a synthesizer of reinforced, integrated and summarized medical knowledge, guide on how to study, and enhancer of physician quantity and/or quality. Medical review centers are viewed as complementary to medical schools. DREEM scores revealed an excellent educational environment. Teachers are strong areas and factual learning, teacher-centered approach, problems with memorization and feelings of loneliness are weak areas. Educational environment was perceived to be tailored-fit for the medical board examinations. Medical review centers are perceived to perform a separate function from medical schools which focus on clinical skills and attitudes while medical review centers focus on board-relevant clinical knowledge. The excellent educational environment of a medical review center enables it to fulfill its perceived roles, which in turn are the basis for student enrolment. A medical review center has an impact on several self-regulatory processes of medical graduates during the board exam preparation and ultimately act as a coach that helps them transition to their professional roles as licensed physicians.